# maths

posted by .

xdy-ydx=sqrt(x^2-y^2)dx

• maths -

wolframalpha shows the steps for arriving at the solution

y = x sinh(ln(x)+c)

## Similar Questions

1. ### calculus

If y is a differentiable function of x, then the slope of the tangent to the curve xy - 2y + 4y^2 = 6 at the point where y=1 is ...... How do I do this?

3. ### Math

How do you find a square root of a number that's not a perfect square?
4. ### Mathematics

sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking.

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
6. ### maths

find equations for the tangent and the normal at P (1n2, 2k) on the curve with equation y=ke^x, where k is a constant. (b) given that y=sin^-1x, show that (1-x^2)d^2y/dx^2-xdy/dx=0
7. ### maths

find equations for the tangent and the normal at P (1n2, 2k) on the curve with equation y=ke^x, where k is a constant. (b) given that y=sin^-1x, show that (1-x^2)d^2y/dx^2-xdy/ dx=0
8. ### Algebra

Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?
9. ### maths

solve the initial value problem of the differential equation (y+sqrt(x^2+y^2))dx-xdy=0,y(3)=4
10. ### maths help sir steve

sir steve what about these i just solved it now i didnt get it if x^2+2xy+3y^2=1 prove that (x+3y)^3d^2y/dx^2+2(x^2+2xy+3y^2)=0 i solve with implicit derivative like these 2x+2(xdy/dx+y)+6ydy/dx=0 2x+2xdy/dx+2y+6ydy/dx=0 2xdy/dx+6ydy/dx=-2y-2x …

More Similar Questions